Electronics Wastewater Sludge Treatment using S/S with Ordinary Portland Cement - T, Irwan,; P, Agamuthu, (Malaysian Journal of Science, 2005)
Ordinary Portland Cement (OPC) with or without Activated Carbon (AC) in varying concentrations was used to solidify/stabilize (S/S) wastewater sludge from an electronics plant. In this research the solidification/stabilization method was used to immobilize heavy metal content. To analyze leachability and leach treatment, TCLP and ANS methods were used. Untreated wastewater sludge contains high concentrations of Fe, Al, Sn, Mn, Cu and Ni. Solidification with OPC reduced the leachable fraction of these heavy metals in the solidified matrix of the wastewater sludge. Based on the Toxicity Characteristics Leachability Procedure (TCLP) and the American Nuclear Society (ANS) 16.1 (modified) leach protocol, the initial pH of the extract was 5.9, however, the pH of the final extract ranged between 6.07 and 6.26. The Leachability Indices ($L_i$) obtained ranged between 4 and 9.1 for cement without AC and 7 to 9.2 with AC, compared to standard guidance value of $L_i$≥6. The resulting solid matrices exhibited a compressive strength ranging from 1 to 7.1 MPa, while the standard requirement is 414 kpa (60 psi). Results show that the solidification and stabilization method can immobilize and reduce heavy metal leaching.